Rare Presentation of Non-Tuberculous Mycobacteria: A Case of Lung Infection with Pleural Effusion - Ventiani, Nadia; Dewi Wahyu F.; Irvan Medison; Dessy Mizarti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Non-tuberculous mycobacteria (NTM) are environmental organisms that can cause pulmonary infections, particularly in individuals with predisposing conditions. While NTM lung disease is increasingly recognized, pleural effusion as a complication remains uncommon, posing diagnostic and therapeutic challenges. This case emphasizes the importance of a high index of suspicion, comprehensive microbiological investigations, and bronchoscopy in the diagnosis of NTM lung disease with pleural effusion. Case presentation: We present the case of a 55-year-old male farmer with a history of smoking, who presented with progressive dyspnea, cough, and constitutional symptoms. Initial investigations suggested tuberculosis, but sputum tests were negative. Chest imaging revealed a right pleural effusion and cavitary lung lesions. Pleural fluid analysis showed an exudative pattern with elevated adenosine deaminase (ADA) but negative for acid-fast bacilli. Bronchoscopy with bronchoalveolar lavage culture yielded Mycobacterium other than tuberculosis (MOTT). The patient was diagnosed with NTM lung disease complicated by pleural effusion and initiated on multidrug therapy. Conclusion: This case highlights the diagnostic challenges of NTM lung disease, particularly when presenting with pleural effusion. A high index of suspicion, comprehensive microbiological investigations, and bronchoscopy are crucial for accurate diagnosis. Prompt initiation of appropriate multidrug therapy is essential for optimal outcomes.